Identification of optimal reference genes in golden Syrian hamster with ethanol‐ and palmitoleic acid‐induced acute pancreatitis using quantitative real‐time polymerase chain reaction - Jinxin Miao; Le Kang; Tianfeng Lan; Jianyao Wang; Siqing Wu; Yifan Jia; Xia Xue; Haoran Guo; Pengju Wang; Yan Li (Animal Models and Experimental Medicine, 2023)
Abstract Background Acute pancreatitis (AP) is a severe disorder that leads to high morbidity and mortality. Appropriate reference genes are important for gene analysis in AP. This study sought to study the expression stability of several reference genes in the golden Syrian hamster, a model of AP. Methods AP was induced in golden Syrian hamster by intraperitoneal injection of ethanol (1.35 g/kg) and palmitoleic acid (2 mg/kg). The expression of candidate genes, including Actb, Gapdh, Eef2, Ywhaz, Rps18, Hprt1, Tubb, Rpl13a, Nono, and B2m, in hamster pancreas at different time points (1, 3, 6, 9, and 24 h) posttreatment was analyzed using quantitative polymerase chain reaction. The expression stability of these genes was calculated using BestKeeper, Comprehensive Delta CT, NormFinder, and geNorm algorithms and RefFinder software. Results Our results show that the expression of these reference genes fluctuated during AP, of which Ywhaz and Gapdh were the most stable genes, whereas Tubb, Eef2, and Actb were the least stable genes. Furthermore, these genes were used to normalize the expression of TNF‐α messenger ribonucleic acid in inflamed pancreas. Conclusions In conclusion, Ywhaz and Gapdh were suitable reference genes for gene expression analysis in AP induced in Syrian hamster.